2004
DOI: 10.1038/sj.hdy.6800561
|View full text |Cite
|
Sign up to set email alerts
|

So close and so different: comparative phylogeography of two small mammal species, the Yellow-necked fieldmouse (Apodemus flavicollis) and the Woodmouse (Apodemus sylvaticus) in the Western Palearctic region

Abstract: In Europe, concordant geographical distribution among genetic lineages within different species is rare, which suggests distinct reactions to Quaternary ice ages. This study aims to determine whether such a discrepancy also affects a pair of sympatric species, which are morphologically and taxonomically closely related but which have slight differences in their ecological habits. The phylogeographic structures of two European rodents, the Yellow-necked fieldmouse (A. flavicollis) and the woodmouse (Apodemus sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
134
1
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(144 citation statements)
references
References 52 publications
8
134
1
1
Order By: Relevance
“…Genetic structure of G. glis.-In contrast to the other studies of European rodents, which reported high levels of genetic divergence (Brunhoff et al 2003;Cosson et al 2005;Deffontaine et al 2005Deffontaine et al , 2009Dubey et al 2007;Fink et al 2004;Searle 2002, 2004;Kotlik et al 2006;Michaux et al 2003Michaux et al , 2005Neumann et al 2005), our results show very low genetic variability in G. glis. The evolutionary trees and haplotype network divide G. glis into 3 wellsupported genetic lineages that have nonoverlapping geographical distributions (with the exception of Sicilian animals occurring in 2 different haplogroups).…”
Section: Discussioncontrasting
confidence: 99%
“…Genetic structure of G. glis.-In contrast to the other studies of European rodents, which reported high levels of genetic divergence (Brunhoff et al 2003;Cosson et al 2005;Deffontaine et al 2005Deffontaine et al , 2009Dubey et al 2007;Fink et al 2004;Searle 2002, 2004;Kotlik et al 2006;Michaux et al 2003Michaux et al , 2005Neumann et al 2005), our results show very low genetic variability in G. glis. The evolutionary trees and haplotype network divide G. glis into 3 wellsupported genetic lineages that have nonoverlapping geographical distributions (with the exception of Sicilian animals occurring in 2 different haplogroups).…”
Section: Discussioncontrasting
confidence: 99%
“…Although based on a small sampling, our data do not support the hypothesis of a refugium located in the Balkan area. This pattern of more stable populations in the Balkans has already been described for the bi-coloured shrew (Crocidura leucodon; Dubey et al, 2007b) and the yellow-necked fieldmouse (Apodemus flavicollis; Michaux et al, 2005). This might be explained by milder climatic conditions prevailing in places farther from the ice sheet.…”
Section: Lebarbenchon Et Alsupporting
confidence: 69%
“…Although diVerent species may have had diVerent refugia, colonisation routes (depending on migration abilities), resilience to environmental change, and stochastic events in their histories, such as local extinction (Hewitt, 2003;Michaux et al, 2005), accumulated data reveal a general picture in Europe involving southern refugia and northward colonisation routes. Locally, mountains and seas acted as signiWcant barriers, isolating populations in diVerent glacial refugia and constraining post-glacial migration routes (Hewitt, 1999;Taberlet et al, 1998).…”
Section: Introductionmentioning
confidence: 99%